Earnings Expectations: The Analysts' Information Advantage. - Kross, William; Ro, Byung (The Accounting Review, 1990)
Investigates the degree to which the superiority of analysts' corporate earnings forecasts is associated with firm characteristics. Analyst advantage over a time-series model to past earnings variability; Relationship between analyst advantage and the amount of coverage in the `Wall Street Journal' newspaper.